EXPERIMENTAL ANALYSIS OF A SCREEN-COVERED GROOVE HEAT PIPE - Krambeck, L.; Bartmeyer, G. A.; Santos, P. H. D.; Alves, T. Antonini (Revista de Engenharia Térmica, 2018)
In this research, a heat pipe with screen-covered groove capillary structure was experimentally analyzed. The heat pipe was manufactured from a copper tube with the external diameter of 9.45mm, inner diameter of 6.20mm, and a total length of 200mm. A Wire Electrical Discharge Machining, or Wire-EDM, was used to manufacture axial microgrooves in the heat pipe. A layer of phosphor bronze mesh #100 completed the capillary structure. Distilled water was the working fluid and the loading filling ratio was 60% of the evaporator volume. The condenser was cooled by air forced convection, the adiabatic section was insulated with fiberglass, and the evaporator was heated by an electrical resistor and it was insulated from the environment with aeronautic insulation. The heat pipe was tested in horizontal position, under different heat loads varying from 5 up to 30W. The experimental results showed that the screen-covered groove worked satisfactorily as a capillary structure.